Industrial and biotechnological applications of red algae: a systematic mapping - Beatriz Cerqueira Morais Fernandes; Caline Suele Rodrigues de Almeida; Isabela Ribeiro Suzano; Sabrinna Silva Rego; Raylane Silva de Alcântara; Elias Nunes de Sena Neto; Isabelly Dálete Ferreira Ribeiro (Acta Scientiarum. Biological Sciences, 2024)
The study aimed to systematically and informatively map the different applications of red algae, as well as to discuss the challenges and opportunities for advancement in this field. Specific knowledge gaps and promising areas were also identified to guide future research and practical applications. Data were collected through four renowned scientific databases: Web of Science, SciELO, ScienceDirect, PubMed, and Scopus. Using specific descriptors, all publications were managed through Zotero, a widely used bibliography manager in the academic community. Rigorous exclusion and inclusion criteria were applied to select specific studies relevant to the object of study. The study initially analyzed over 47,000 studies on red algae and their applications in biotechnological industry, but only 23 were considered relevant after careful screening. The diversity of red algae species explored in the studies reflects their potential in several research areas such as health, agriculture, and the environment. Gracilaria sp. emerged as a prominent species, especially in agar production. Bibliometric analysis revealed a predominance of high-quality studies in high-impact journals, mainly related to the antioxidant activity of algae. However, significant gaps were identified in areas such as cosmetics, genetics, and energy production, suggesting opportunities for future research and development. Based on the conducted study, it is evident that red algae offer a diversified range of biotechnological and industrial applications, with opportunities for exploration in environmental, health, and agricultural sectors. Although some fields are not yet widely disseminated, the collected data provide guidance to direct future research and practical applications, promoting significant advances in the field of biotechnology.